2008
DOI: 10.1177/1359105308088517
|View full text |Cite
|
Sign up to set email alerts
|

The Affective Impact of Exercise Intensity That Slightly Exceeds the Preferred Level

Abstract: We examined the affective consequences of an exercise intensity that slightly exceeded the preferred level. Twenty-five middle-age sedentary women participated in two 20-min treadmill exercise bouts, one during which they could select the speed and one during which the speed was 10 per cent higher than the selfselected. During the bout at selfselected intensity, ratings of pleasure remained stable, whereas during the imposed-intensity bout pleasure decreased. Therefore, even a minor increase in exercise intens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
88
0
2

Year Published

2010
2010
2014
2014

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(95 citation statements)
references
References 25 publications
5
88
0
2
Order By: Relevance
“…High interindividual variability has been recorded when individuals are prescribed intensities that would be described as moderate (46%-63% V02max) (3), with some individuals reporting positive affective responses and some reporting negative (34,35,40). Furthermore, when exercise intensity is prescribed and exceeds the preferred intensity by a small degree (e.g., 10% higher than the preferred intensity), affective responses decrease significantly (16,28). According to the dual-mode theory, which can explain the affective responses to the exercise stimulus, this variability and pattem of responses is due to the interplay between cognitive factors (e.g., personality, competence, experience) and interoceptive (e.g., muscular, respiratory) cues and how the cues are interpreted.…”
mentioning
confidence: 99%
“…High interindividual variability has been recorded when individuals are prescribed intensities that would be described as moderate (46%-63% V02max) (3), with some individuals reporting positive affective responses and some reporting negative (34,35,40). Furthermore, when exercise intensity is prescribed and exceeds the preferred intensity by a small degree (e.g., 10% higher than the preferred intensity), affective responses decrease significantly (16,28). According to the dual-mode theory, which can explain the affective responses to the exercise stimulus, this variability and pattem of responses is due to the interplay between cognitive factors (e.g., personality, competence, experience) and interoceptive (e.g., muscular, respiratory) cues and how the cues are interpreted.…”
mentioning
confidence: 99%
“…Freedom to choose exercise intensity positively influences affective response to exercise, which then positively influences exercise adherence . Research has suggested that self-selected exercise intensity results in more positive affect as compared to prescribed exercise intensity (Lind, Vazou, & Ekkekakis, 2008;Parfitt & Gledhill, 2004;VazouEkkekakis & Ekkekakis, 2009). Lind et al (2008) compared self-selected versus prescribed exercise intensity by using two 20 minute treadmill sessions.…”
Section: Motivation and Goalsmentioning
confidence: 99%
“…Research has suggested that self-selected exercise intensity results in more positive affect as compared to prescribed exercise intensity (Lind, Vazou, & Ekkekakis, 2008;Parfitt & Gledhill, 2004;VazouEkkekakis & Ekkekakis, 2009). Lind et al (2008) compared self-selected versus prescribed exercise intensity by using two 20 minute treadmill sessions. A sedentary sample of 25 middle-aged women was allowed to self-select exercise intensity in the first session, and the intensity of the second session was 10% higher than the first session.…”
Section: Motivation and Goalsmentioning
confidence: 99%
“…This quote is in my opinion a valuable illustration of the use of physical activity to reduce negative affects, and that sometimes the physical activity has to be of certain intensity for the individual to achieve the intended effect. Therefore, it is a paradox that vigorous intensity physical activity performed in excessive amounts actually can worsen mood (Lind, Ekkekakis, & Vazou, 2008). Why the exercise dependent individuals prefer vigorous intensity physical activity is still not explored adequately.…”
Section: Characteristics Of Exercise Dependence: High Intensity Activmentioning
confidence: 99%